2022
DOI: 10.1002/brb3.2668
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adverse childhood experiences and their relationship to mental and physical illnesses in the Eastern Region of Saudi Arabia

Abstract: Introduction: Adverse childhood experiences (ACEs) are widely prevalent and interrelated. They affect multiple domains of health while having a dose-response effect.These effects are biologically plausible, where ACEs are found to be highly associated with physical and mental comorbidities. Objectives:The study aimed to measure the magnitude of ACE and its relationship to mental and physical illnesses in the Eastern Region of Saudi Arabia by assessing its prevalence. Materials and Methods:This was a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…Global evidence suggested that exposure to ACEs increases the risk of developing anxiety disorders during both adolescence and adulthood (Kaminer et al, 2022; Sahle et al, 2022; Zarse et al, 2019). Our analysis showed ACEs had a significant, direct association with the presence of anxiety disorders and the comorbidity of anxiety and mood disorders, similar to results from Saudi Arabia and elsewhere (AlHemyari et al, 2022; Alhowaymel & Alenezi, 2022; Almuneef et al, 2017; Kessler et al, 2010; McCutchen et al, 2022; Zarse et al, 2019). However, the association was stronger for certain types of ACEs (e.g., physical or sexual abuse), while others had a weaker association (e.g., family violence) or did not reach statistical significance (e.g., family economic adversity).…”
Section: Discussionsupporting
confidence: 87%
“…Global evidence suggested that exposure to ACEs increases the risk of developing anxiety disorders during both adolescence and adulthood (Kaminer et al, 2022; Sahle et al, 2022; Zarse et al, 2019). Our analysis showed ACEs had a significant, direct association with the presence of anxiety disorders and the comorbidity of anxiety and mood disorders, similar to results from Saudi Arabia and elsewhere (AlHemyari et al, 2022; Alhowaymel & Alenezi, 2022; Almuneef et al, 2017; Kessler et al, 2010; McCutchen et al, 2022; Zarse et al, 2019). However, the association was stronger for certain types of ACEs (e.g., physical or sexual abuse), while others had a weaker association (e.g., family violence) or did not reach statistical significance (e.g., family economic adversity).…”
Section: Discussionsupporting
confidence: 87%
“…In a pilot study conducted in Riyadh, Saudi Arabia, the authors found that most participants reported experiencing one or more ACEs, and almost a third of the participants had experienced four or more ACEs [ 28 ]. Another study conducted to evaluate the prevalence and connection of ACEs with both physical and mental diseases in eastern Saudi Arabia found that the majority of study participants (81.8%) had experienced four or more ACEs, with emotional neglect being the most prevalent ACE type (82.2%) [ 29 ]. Additionally, women with four or more ACEs were at higher risk of insomnia, stress, and depression, which aligns with other previous studies [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, women with four or more ACEs were at higher risk of insomnia, stress, and depression, which aligns with other previous studies [ 20 , 21 ]. Compared to those with only one ACE, those with four or more ACEs are more likely to experience physical diseases [ 29 ]. Studies conducted in Saudi Arabia comparing people with ACEs to those without ACEs revealed a two-fold greater risk of physical health problems such as hypertension, T2DM, coronary heart disease, and obesity among people with ACEs [ 13 , 30 , 31 ], agreeing with another study conducted in Saudi Arabia [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Saudi context, ACEs have received attention from the Saudi government, which enacted the Law of Protection from Abuse legislation (“Bureau of Experts at the Council of Ministers ‐ Kingdom of Saudi Arabia,” 2013). It is estimated that 82% of Saudi adults reported at least one ACE (Almuneef et al, 2014), impacting different aspects of their health (AlHemyari et al, 2022; Almuneef et al, 2017). There is only one study that included Saudi adolescents aged between 15 and 19 and found that 64% experienced ACEs (Al‐Eissa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%